Placental transverse relaxation time (T2) estimated by MRI: Normal values and the correlation with birthweight. (25th December 2020) - Anderson, Kristi B.; Andersen, Anna S.; Hansen, Ditte N.; Sinding, Marianne; Peters, David A.; Frøkjær, Jens B.; Sørensen, Anne
Abstract: Introduction: Placental transverse relaxation time (T2) assessed by MRI may have the potential to improve the antenatal identification of small for gestational age. The aims of this study were to provide normal values of placental T2 in relation to gestational age at the time of MRI and to explore the correlation between placental T2 and birthweight. Material and methods: A mixed cohort of 112 singleton pregnancies was retrieved from our placental MRI research database. MRI was performed at 23.6‐41.3 weeks of gestation in a 1.5T system (TE (8): 50‐440 ms, TR: 4000 ms). Normal pregnancies were defined by uncomplicated pregnancies with normal obstetric outcome and birthweight deviation within ±1 SD of the expected for gestational age. The correlation between placental T2 and birthweight was investigated using the following outcomes; small for gestational age (birthweight ≤−2 SD of the expected for gestational age) and birthweight deviation (birthweight Z ‐scores). Results: In normal pregnancies (n = 27), placenta T2 showed a significant negative linear correlation with gestational age ( r = −.91, P = .0001) being 184 ms ± 15.94 ms (mean ± SD) at 20 weeks of gestation and 89 ms ± 15.94 ms at 40 weeks of gestation. Placental T2 was significantly reduced among small‐for‐gestational‐age pregnancies (mean Z ‐score −1.95, P < .001). Moreover, we found a significant positive correlation between placenta T2 deviation ( Z ‐score) and birthweight deviation ( Z ‐score) ( R 2 = .26, P = .0001). Conclusions: This study provides normal values of placental T2 to be used in future studies on placental MRI. Placental T2 is closely related to birthweight and may improve the antenatal identification of small‐for‐gestational‐age pregnancies.